Case Report: Diagnosis of Klebsiella pneumoniae Invasive Liver Abscess Syndrome With Purulent Meningitis in a Patient From Pathogen to Lesions - Zeng, Sheng; Yan, Wei-qian; Wu, Xiao-mei; Zhang, Hai-nan (Frontiers in Medicine, 2021)
As a determinant human pathogen, Klebsiella pneumoniae is known to cause rare K. pneumoniae liver abscess syndrome (KLAS) which was more common in Asia in early-stage and reported increasingly outside Asia now. Patients with KLAS who have septic metastatic ocular or central nervous system (CNS) lesions are associated with high morbidity and mortality. Relatively infrequent adult community-acquired K. pneumoniae meningitis have been documented and most were with poor prognosis. In this paper, we reported a case of KLAS presenting purulent meningitis as disease onset. While negative results were obtained in the bacterial culture of CSF, blood, or liver pus, metagenomic next-generation sequencing (mNGS) of CSF, and blood samples which were synchronously performed demonstrated Klebsiella pneumoniae as the pathogenic microorganism (13,470 and 5,318 unique reads, respectively). The ultimately cured patient benefited from rapid pathogen diagnosis, early percutaneous drainage of the abscess, and prompt appropriate antibiotic administration. Our case highlights the importance of clinicians using mNGS for early pathogen diagnosis of this disease.